Prevalence, typology and clinical correlates of sexual dysfunction among men with alcohol dependence syndrome - Anil Kumar Buruganahalli Nagendrappa; Shalini Mallanna; Sanjay Raj G.; D.R. Prasannakumar (International Journal of Medical Research and Review, 2016)
Background: Chronic and persistent alcohol use is known to induce sexual dysfunction, but it is often unexplored and untreated in routine clinical practice.Objective: To study the prevalence and typology of sexual dysfunction and its clinical correlates among male patients seeking treatment for alcohol dependence.Materials and Methods: 60 male subjects (aged 18-50 years) meeting the criteria for alcohol dependence syndrome (ADS), according to DSM-IV were enrolled for the study. Data regarding socio- demographic and clinical details were recorded on a semi-structured proforma designed for the study. They were assessed for sexual dysfunction using a Sexual Dysfunction Checklist, constructed using items from the Diagnostic Criteria for Research (ICD-10) for sexual dysfunction and Arizona Sexual Experience Questionnaire (ASEX) and for severity of alcohol dependence using the Severity of Alcohol Dependence Questionnaire (SADQ).Results: 58.3 % had one or more sexual dysfunction as per ASEX, the most common being inability to reach orgasm (60%), dissatisfaction with orgasm (58.3%) and erectile dysfunction (56.7%). As per sexual dysfunction checklist, dissatisfaction with own sexual performance (58.3%), anorgasmia (56.7%) and erectile dysfunction (53.3%) were the most common. Longer duration of alcohol consumption and dependence, high levels of intake and sever dependence appeared to be the most significant predictors of developing sexual dysfunction.Conclusion: SD is highly prevalent in patients with alcohol dependence and all domains of sexual functioning are affected. Anorgasmia is quite common in patients with alcohol dependence. Longer duration of consumption and dependence and heavy drinking proportionately increases the risk. Clinicians need to routinely evaluate sexual functioning in alcoholic patients and address the same.